Inspiratory Efforts, Positive End-Expiratory Pressure, and External Resistances Influence Intraparenchymal Gas Redistribution in Mechanically Ventilated Injured Lungs - Pellegrini, Mariangela; Hedenstierna, Göran; Larsson, Anders Sune; Perchiazzi, Gaetano (Frontiers in Physiology, 2021)
Background. Potentially harmful lung overstretch can follow intra-parenchymal gas redistribution during mechanical ventilation. We hypothesized that inspiratory efforts characterizing spontaneous breathing, positive end-expiratory pressure (PEEP) and high inspiratory resistances influence inspiratory intra-parenchymal gas redistribution. Methods. This was an experimental study conducted on a swine model of mild acute respiratory distress syndrome. Dynamic computed tomography and respiratory mechanics were simultaneously acquired at different PEEP levels and external resistances, during both spontaneous breathing and controlled mechanical ventilation. Images were collected at two cranial-caudal levels. Delta-volume images (ΔVOLs) were obtained subtracting pairs of consecutive inspiratory images. The first three ΔVOLs, acquired for each analyzed breath, were used for the analysis of inspiratory pendelluft defined as intra-parenchymal gas redistribution before the start of inspiratory flow at the airway opening. The following ΔVOLs were used for the analysis of gas redistribution during ongoing inspiratory flow at the airway opening. Results. During the first flow-independent phase of inspiration, pendelluft of gas was observed only during spontaneous breathing and along the cranial-to-caudal and non-dependent-to-dependent directions. The pendelluft was reduced by high PEEP (p < 0.04 comparing PEEP 15 and PEEP 0 cmH2O) and low external resistances (p < 0.04 comparing high and low external resistance). During the flow-dependent phase of inspiration, two patterns were identified: 1. gas displacing characterized by large gas redistribution areas; 2. gas scattering characterized by small, numerous areas of gas redistribution. Gas displacing was observed at low PEEP, high external resistances and it characterized controlled mechanical ventilation (p < 0.01, comparing high and low PEEP during controlled mechanical ventilation). Conclusions. Low PEEP and high external resistances favored inspiratory pendelluft. During the flow-dependent phase of the inspiration, controlled mechanical ventilation, low PEEP and high external resistances favored larger phenomena of intra-parenchymal gas redistribution (gas displacing) endangering lung stability.